Quality Determinants of Corporate Governance Practices of Brazilian Companies of Traded that Have Public Investment - Almeida, Moisés Araújo; Santos, Joséte Florêncio dos; Ferreira, Lúcio Flávio Vieira de Medeiros; Torres, Fernando José Vieira (Review of Business Management, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The adoption of good practices of corporate governance allows transparent management, diminishing the asymmetry of information and the agency conflict. This article investigates the determinants of the corporate governance quality on Brazilian companies with public investment. The sample of the research was constituted by 35 firms for the year 2005 and 34 firms for the year 2006, with public information available on CVM database. It was used econometric techniques of multiple linear regression with application of the ordinary least squares. The results show that the major part of the analyzed companies presents levels of governance above the average. Also, it is evidenced that the greater ownership concentration in the hands of a single shareholder influences positively the corporate governance index, as well as the leverage, tangibility, growth and age, impact negatively on the quality of governance practices. Key words: <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->Corporate governance. Public companies. Public investment.